Oral Administration of Flavonifractor plautii, a Bacteria Increased With Green Tea Consumption, Promotes Recovery From Acute Colitis in Mice via Suppression of IL-17 - Mikami, Ayane; Ogita, Tasuku; Namai, Fu; Shigemori, Suguru; Sato, Takashi; Shimosato, Takeshi (Frontiers in Nutrition, 2021)
Flavonifractor plautii (FP) has been reported to participate in the metabolism of catechins in the human gut. However, there is limited information on the immune regulatory effects of this bacterium. We confirmed that the administration of green tea increases the abundance of FP in the gut microbiota and investigated the effect of FP in a mouse colitis model. Mice were orally administered FP for 10 consecutive days; colonic inflammation was evaluated daily on the basis of stool consistency, gross rectal bleeding, and body weight. In the dextran sodium sulfate model, FP-exposed animals exhibited lower levels of inflammation and strong inhibition of IL-17 signaling. Moreover, lipoteichoic acid from FP was identified as the active component mediating IL-17 suppression. Thus, oral administration of FP appears to modulate gut inflammation, and represents a viable and inexpensive oral microbial therapeutic.